ANALISIS PENGUKURAN KINERJA KEUANGAN NU CARE – LAZISNU TAHUN 2017-2018 : BERDASARKAN RASIO KEUANGAN ORGANISASI PENGELOLA ZAKAT MENURUT BAZNAS - Purnamasari, Linda Mauliani (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2022)
NU CARE - LAZISNU is responsible to the government and the community in the management of Zakat, Infaq, and Alms. This study aims to measure the financial performance of NU CARE - LAZISNU using the financial ratios of the Zakat Management Organization issued by BAZNAS (2019). The object used in this study is the NU CARE-LAZISNU financial statements for 2017 and 2018. The ratio component used is the ratio according to BAZNAS (2019), namely: activity ratio, efficiency ratio, amil fund ratio, liquidity ratio, and growth ratio. Based on the measurement results, the financial performance of NU - CARE LAZISNU in 2017 and 2018 was stated to be good.